Perceptions of Early Career Researchers Regarding Competence Development - Villardón-Gallego, Lourdes (2018)
Doctoral studies lead to the highest level of academic qualification, promoting the development of competences that enable individuals to perform as leaders in the generation of scientific knowledge and its application in the improvement of society, through research and innovation. The process of acquiring competences involves a demanding and long-lasting training path that entails difficulties that must be overcome with the help of both personal and contextual factors. In this research, information has been gathered on the perceptions of trainee researchers (8 participants: 5 women and 3 men) regarding the learning process at the three moments of the doctoral program: learning expectations, difficulties and resources at the beginning, difficulties and support experienced, as well as partial learning perceived in the process, and learning perceived at the end, once the doctoral thesis has been defended and approved. The results have made it possible to identify the fundamental contextual and individual aspects in each of the three moments of the researchers’ training. These findings have important implications for the planning and development of doctoral training programs.